Call variation of Crested Francolin (Dendroperdix sephaena) across Africa defies the effects of spatial gradients. (25th March 2021) - Van Niekerk, Johann H.; Megía‐Palma, Rodrigo; Forcina, Giovanni
Abstract : The study of intraspecific geographical variation of non‐passerine vocalizations remains under‐studied, especially in African species. We explored spatial patterns in call variation of the Crested Francolin Dendroperdix sephaena across its wide sub‐Saharan distribution in Africa. We extracted and compared 152 pair duets from 44 recordings encompassing four D. sephaena subspecies and, in the field, played back each subspecies' vocalizations to 15 D. s. sephaena and three D .  s .  zambesiae males to document their behaviour. We recorded strong responses to con‐subspecific calls and weak responses to hetero‐subspecific calls, especially towards D . s. grantii and D. s. rovuma . This indicates that intraspecific vocal variability in D. sephaena is not clinal but spatially discrete, and strictly reflects subspecies affiliation (albeit with more similar vocal features among geographically neighbouring subspecies). Vocal variation in D. sephaena may have evolved under palaeoclimatic events that fragmented its former range and promoted allopatric diversification before a re‐expansion into partial sympatry.